Evaluating the associations between serum vitamin D levels and dental caries (ICDAS index) among dental students of Tehran university of medical sciences - Fereshteh Abbaspour; Mahdia Gholami; Katayoun Sargeran (Tehran University of Medical Sciences, 2020)
Background and Aims: Dental caries is a multifactorial and common disease that leads to a decrease in the quality of life of individuals. The aim of this study was to determine the relationship between serum vitamin D and dental caries in the third year-to-last year students of dental school of Tehran University of Medical Sciences. Materials and Methods: This descriptive cross-sectional study was conducted on 123 dental students. Demographic and health information were completed through a checklist. The level of vitamin D in individuals was measured by blood sampling. We recorded caries by ICDAS (international caries detection and assessment system) in two levels of D(1-6)MFT (total of decayed, filled and missing tooth) and D(3-6)MFT (total of progressive decayed, filled and missing tooth). Data analysis was done by the SPSS package version 25 using statistical tests of correlation and regression. Results: The results showed that the correlation coefficient between vitamin D and caries index D(1-6)MFT was -0.89 with a P-value of 0.3328 which was not statistically significant. Based on the backward logistic regression, there was a positive significant statistical association between the D(3-6)MFT with vitamin D deficiency (P<0.001), weight (P=0.012), dental visit (P=0.023) and frequency of sweet snack consumption (P=0.03). In addition a significant and inverse statistical association was reported between the D(3-6)MFT and milk consumption (P=0.026). Conclusion: Among dentistry students, no relation between vitamin D deficiency and early stages of decay was seen, however this relation was statistically significant in regard with progressive dental caries.